Decoding the Sino-North Korean borderlands - Cathcart, Adam; Green, Christopher (Christopher K.); Denney, Steven; Van Schendel, Willem; Harris, Tina (Asian borderlands., 2021)
In the past decade, the Chinese-North Korean border region has undergone a gradual transformation into a site of intensified cooperation, competition, and intrigue. These changes have prompted a significant volume of critical scholarship and media commentary across multiple languages and disciplines. Drawing on existing studies and new data, this volume brings much of this literature into concert by pulling together a wide range of insight on the region's economics, security, social cohesion, and information flows. Drawing from multilingual sources and transnational scholarship, the volume is enhanced by the extensive fieldwork undertaken by the editors and contributors in their quest to decode the borderland. In doing so, the volume emphasizes the link between theory, methodology, and practice in the field of Area Studies and social science more broadly.